2020
DOI: 10.1097/md.0000000000023416
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Danlou tablet for the treatment of stable angina pectoris

Abstract: Introduction: Stable angina pectoris has a high prevalence and causes serious harm. Revascularization therapy can relieve angina pectoris to some extent, but it is not widely accepted in China due to the cost and secondary events. The Chinese proprietary medicine Danlou tablet has been widely used to treat angina pectoris, but previous trials had inadequate methodologies. In this study, we aim to conduct a randomized controlled trial to evaluate its efficacy and safety on stable angina. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Danlou tablets are composed of Danshen ( Radix Salviae Miltiorrhiae ), Gualou ( Fructrs Trichosanthis ), Gegen ( Radix Puerariae ), Chishao ( Radix Paeoniae Rubra ), Xiebai ( Bulbus Allii Macrostemi ), Chuanxiong ( Rhizoma Chuanxiong ), Yujin ( Radix Curcumae ), Zexie ( Rhizoma Alismatis ), Huangqi ( Radix Astragali ), and Gusuibu ( Rhizoma Drynariae ), which has the effect of relieving chest, dispelling phlegm, dispersing knot, and activating blood to remove stasis. Therefore, it plays a good role in treating CHD of blood stasis and phlegm turbidimetry syndromes ( 41 ). Experimental studies have fully exemplified that Danlou tablets can reduce myocardial ischemia and reperfusion injury ( 42 ), regulate procholesterol efflux, and perform anti-inflammation by activating the PPAR α /ABCA1 signaling pathway; concurrently, the NF-κB signaling pathway is prevented, thereby playing its role in alleviating atherosclerosis ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Danlou tablets are composed of Danshen ( Radix Salviae Miltiorrhiae ), Gualou ( Fructrs Trichosanthis ), Gegen ( Radix Puerariae ), Chishao ( Radix Paeoniae Rubra ), Xiebai ( Bulbus Allii Macrostemi ), Chuanxiong ( Rhizoma Chuanxiong ), Yujin ( Radix Curcumae ), Zexie ( Rhizoma Alismatis ), Huangqi ( Radix Astragali ), and Gusuibu ( Rhizoma Drynariae ), which has the effect of relieving chest, dispelling phlegm, dispersing knot, and activating blood to remove stasis. Therefore, it plays a good role in treating CHD of blood stasis and phlegm turbidimetry syndromes ( 41 ). Experimental studies have fully exemplified that Danlou tablets can reduce myocardial ischemia and reperfusion injury ( 42 ), regulate procholesterol efflux, and perform anti-inflammation by activating the PPAR α /ABCA1 signaling pathway; concurrently, the NF-κB signaling pathway is prevented, thereby playing its role in alleviating atherosclerosis ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used to treat coronary artery disease in China for a long time. Relevant clinical research demonstrated that DL can treat stable angina pectoris, alleviate adverse left ventricular remodeling after myocardial infarction, and reduce the peri-procedural myocardial injury among patients undergoing PCI for non-ST elevation acute coronary syndrome ( Wang et al, 2015 ; Mao et al, 2016 ; Yang et al, 2020 ; Zhao et al, 2021 ).…”
Section: Clinical Applicationmentioning
confidence: 99%
“…Danlou tablet (Dan), a well-known compound preparation that contains 10 Chinese herbal medicines ( Trichosanthes kirilowii Maxim , Allium macrostemon Bunge , Radix Puerariae , Ligusticum chuanxiong hort , Salvia miltiorrhiza Bunge , Curcumae Radix , Astragalus propinquus Schischkin , Davallia mariesii Moore ex Bak , Alisma plantago-aquatica Linn , Paeoniae Radix Rubra ), is widely used to treat angina pectoris [ 16 ]. In the past decades, evidence has shown that Dan confers cardioprotective effects.…”
Section: Introductionmentioning
confidence: 99%